Revisiting Laportea: Quercetin as A Key Bioactive for Natural Diabetes Therapy - Muhammad Nurul Fadel; Arifah Sri Wahyuni; Rima Munawaroh (Indonesian Journal of Global Health Research, 2026)
Insulin injections and oral hypoglycemic drugs are the main therapies available for the treatment of diabetes. However, side effects and dependence make many sufferers not continue treatment. The development of plant-based antidiabetic alternatives continues, one of which is the genus Laportea, which contains flavonoids and derivative compounds, such as quercetin, that are able to control blood sugar.  The purpose of this literature review is to provide evidence-based information on the potential content of quercetin in Laportea. This literature review was created by searching databases such as: Pubmed, Elsevier, Science Direct, and Google Scholar. Searches on Elsevier and google Scholar were conducted using the following keywords: "quercetin AND Laportea decumana", "quercetin AND Laportea aestuans", "quercetin AND Laportea bulbifera" "Flavanoid AND quercetin AND Laportea". "quercetin AND antidiabetic". Meanwhile, the keywords to search for articles on pubmed are done by writing quercetin AND Laportea [MeSH]", "Flavanoid AND quercetin AND Laportea [MeSH]". "quercetin AND antidiabetic [MeSH]". The search was conducted on articles published in 2010-2025. The search was conducted on articles published in 2015-2025. Articles are selected and reviewed according to the theme and research questions by all researchers. Quercetin provides superior hypoglycemic effects and insulin sensitization activity by promoting pancreatic cell-β proliferation and by increasing glucose metabolism and insulin secretion. previous studied reported that the administration of 20 mmol· L-1 QE to pancreatic β cells INS-1 increases insulin secretion induced by glucose and gliclazide and protects β cells against oxidative damage. The results of this review literature have explained that the benefits of the laportea plant to overcome diabetes are the content  of Quercetin which can provide a superior hypoglycemic effect.